TREATMENT OF EFFLUENT FROM DYEING INDUSTRY USING ADSORPTION TECHNIQUE - POPURI ASHOK KUMAR; PAGALA BANGARAIAH (International Journal of Pharma and Bio Sciences, 2014)
Rapid industrialization coupled inadequate environmental management in the developed countries resulted in large scale pollution of the environment especially the aquatic environment with a multitude of contaminants. Increasing complexities of the contaminants rendered the conventional treatment systems ineffective and warrants a more sophisticated plan of attack for removal of specific pollutants. Recent advances in contemporary environmental engineering focus attention on effective treatment methodologies to meet the requirements in both environmentally acceptable and cost effective manners. Discharge of colored effluent is dissented even by the general public on the presumption that the color is indicative of the pollution. Discharge of such partially treated effluent, in addition to imparting color to the receiving waters, also renders them unfit for its intended beneficial use. Moreover, recent reports suggests toxic nature of color causing substances serve as carriers of heavy metals since they have a tendency to form a chelate complex with most of the heavy metal ions. Recognition of color levels coupled with the public awareness calls for a comprehensive approach and research efforts to solve the problem of color pollution and control. Among several industries that contribute colored effluent, textile, dye manufacturing, pulp & paper, tanneries are the most. Adsorption onto different adsorbents which is a sludge free process is recommended.